P118 "LARCing about" with integrated services: Our genitourinary medicine (GUM) service users' views on the provision of short & long acting reversible contraception (LARC). (30th June 2016) - McIntosh, Rachel; Burnett, Kerry; Peter, Elisha; Walsh, Sam; Forbes, Kimberley; Nicholas, Donna; Gupta, Divya; Avery, Gillian; Cohen, Charlotte E; Nwokolo, Nneka; Day, Sara
Abstract : Background: Integrated models are promoted as the ideal way for women to receive sexual health and contraception. Commissioners advocate shifting contraceptive provision away from GUM to general practice and community settings. Given our boroughs have the lowest GP LARC prescribing rates in England, we are concerned about compromised access to contraception and a consequent rise in unplanned pregnancy/abortion rates. Aim: To explore our service users' preferences and experiences of accessing contraception. Methods: Between January and February 2016, an anonymised questionnaire was offered to all patients requesting contraception from four integrated GUM clinics. Results: 329 patients (median age 20–30 years) returned their questionnaire. 52%, 19% and 28% of users attended short-acting contraception, sub-dermal implant or intrauterine device (IUD) appointments respectively. 83% respondents found our service easy/very easy to access. Median LARC waiting time was 1–2 weeks. 33/86 (38%) of non-LARC and 29/109 (27%) of LARC (34% IUD, 21% implant) users experienced problems obtaining contraception elsewhere with 88% citing their GP had no suitable appointment or didn't offer their chosen method. 77% (126/164) of respondents prefer to have their sexual health and contraceptive needs met together, whilst 6% prefer separate settings. Patients prefer obtaining contraception from: GUM(46%); GP(19%); community clinics(16%); private establishments/online(6%); no clear preference(13%). 34% of users would consider accessing LARC privately. Conclusion: Two fifths of patients had difficulty accessing any form of contraception outside of GUM, most appreciate a one-stop shop approach and half prefer GUM to be their contraceptive provider. This survey demonstrates the need to preserve GUM as a contraceptive provider.